The effect of educational intervention based on theory of planned behavior on mothers' skills in sexual care of children - Ali Khani Jeihooni; Arman Moradi; Asiyeh Yari; Amin Kiyani; Pooyan Afzali Hasirini (BMC, 2022)
Abstract Background The parent's and especially the mothers' skills play a major role in the the education of healthy sexual behaviors in children. This study investigates the effect of educational intervention based on the Theory of Planned Behavior (TPB) on mothers' skills in the sexual care of children in Fasa city, Fars province, Iran in 2019. Methods This study was a quasi-experimental intervention with a control group. 200 mothers of children aged 5 to 6 years in Fasa preschool were selected using a multi-stage random sampling method and were divided into two groups of intervention (100) and control (100). After providing a pre-test to both groups, only the experimental group received training on sexual care of children's abilities based on the Theory of Planned Behavior constructs. The educational intervention consisted of seven 55-60-minute sessions in which the presenter gave a presentation, asked and answered questions, and used posters, brochures, films, animations, and PowerPoints. Both groups completed the questionnaire three months following the intervention. A questionnaire and Theory of planned behavior constructs were used to collect information. The data was analyzed with SPSS22 software using paired t-tests, Chi-square tests, and independent t-tests, with a significance level of 0.05. Results Before the intervention, there was no significant difference in the constructs of theTheory of planned behavior between the two groups (p>0.05), but after the intervention, knowledge scores from 8.33±2.97 to 20.67±2.84, attitude scores from 29.80±4.27 to 62.22±4.34, subjective norms from 20.12±4.55 to 42.28±4.20, perceived behavioral control from 20.24±4.36 to 42.88±4.52, behavioral intention from 3.24±1.60 to 7.44±1.59 and behavior from 2.98±1.13 to 8.14±1.08 in the intervention group (p< 0.001). Conclusion This study showed TPB constructs' Effectiveness in adopting the level of mothers' skills in the sexual care of children. Hence, this model can act as a framework for designing and implementing educational interventions for the sexual care of children.